2020
DOI: 10.1038/s41598-020-62181-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Aβ42 fibrils adopt similar secondary structure but differ in cross-strand side chain stacking interactions within the same β-sheet

Abstract: Formation of polymorphic amyloid fibrils is a common feature in neurodegenerative diseases involving protein aggregation. In Alzheimer's disease, different fibril structures may be associated with different clinical sub-types. Structural basis of fibril polymorphism is thus important for understanding the role of amyloid fibrils in the pathogenesis and progression of these diseases. Here we studied two types of Aβ42 fibrils prepared under quiescent and agitated conditions. Quiescent Aβ42 fibrils adopt a long a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…The observations that highly twisted fibrils can be observed in the CAA/ad case, the CAA/s case, and in the cryo-EM study suggest that the short, flat generation-0 fibrils adopt this twisted morphology when not interacting with adjacent fibrils or protofibrils. In the case of Aβ42 fibrils that can adopt both twisted fibrils and flat, laterally associated fibrils, electron paramagnetic resonance measurements indicate that the fibrils have the same secondary structure, but the laterally associated fibrils have stronger side chain interactions along the length of the Aβ sequence ( 37 ). In the cryo-EM study on fibrils derived from vascular amyloid ( 36 ), several polymorphs were observed, which the authors proposed had same internal fold and were distinguished by lateral association.…”
Section: Discussionmentioning
confidence: 99%
“…The observations that highly twisted fibrils can be observed in the CAA/ad case, the CAA/s case, and in the cryo-EM study suggest that the short, flat generation-0 fibrils adopt this twisted morphology when not interacting with adjacent fibrils or protofibrils. In the case of Aβ42 fibrils that can adopt both twisted fibrils and flat, laterally associated fibrils, electron paramagnetic resonance measurements indicate that the fibrils have the same secondary structure, but the laterally associated fibrils have stronger side chain interactions along the length of the Aβ sequence ( 37 ). In the cryo-EM study on fibrils derived from vascular amyloid ( 36 ), several polymorphs were observed, which the authors proposed had same internal fold and were distinguished by lateral association.…”
Section: Discussionmentioning
confidence: 99%
“…The EPR spectrum of Aβ42 L34R1 fibrils in the absence of EGCG is characteristic of the parallel in-register β-sheet structure. The EPR spectra in the presence of 10× and 50× EGCGs have a similar line shape compared to those of the no-EGCG sample (Figure C), suggesting that EGCG did not change the structure of Aβ42 fibrils. Previously, we have obtained the EPR spectra of Aβ42 globulomers (Figure D) and prefibrillar oligomers (Figure E) spin-labeled at the same residue position.…”
Section: Resultsmentioning
confidence: 97%
“…In the fibrils, the EPR spectral lines are much broader, resulting in greatly reduced spectral amplitude. Another characteristic of the fibril spectrum is that the three EPR resonance lines collapse toward the center line as a result of the spin exchange interaction in the parallel in-register β-sheet structure of Aβ fibrils [ 33,34]. Therefore, even though the Aβ globulomers have a strong tendency to bind to each other, the structures remain unchanged and are very different from the structures in fibrils.…”
Section: Resultsmentioning
confidence: 99%